AAV-mediated TIMP-1 overexpression in aortic tissue reduces the severity of allograft vasculopathy in mice - Remes, Anca; Franz, Maximilian; Zaradzki, Marcin; Borowski, Christopher; Frey, Norbert; Karck, Matthias; Kallenbach, Klaus; Müller, Oliver J.; Wagner, Andreas H.; Arif, Rawa (The journal of heart and lung transplantation, 2020)
Background: Allograft vasculopathy (AV) is the primary limiting factor for long-term graft survival. An increased activity of matrix metalloproteinases (MMPs) contributes to neointima formation in AV and represents a potential therapeutic target. Adeno-associated virus (AAV)-mediated gene therapy comprises a potentially benign vector model for the long-term expression of MMP antagonists. - Methods: Aortic allografts from DBA/2 mice were incubated with control buffer, AAV-enhanced green fluorescence protein (EGFP), or tissue inhibitor of metalloproteinases 1 (TIMP-1)-loaded AAV (AAV-TIMP-1) and transplanted into the infrarenal aorta of C57BL/6 mice. Cyclosporine A (10 mg/kg body weight) was administered daily. Explantation as well as histomorphometric and immunohistochemical evaluation was performed after 30 days. Matrix metalloproteinase (MMP) activity was visualized by gelatin in situ zymography. - Results: Intima-to-media area ratio and neointima formation were significantly reduced in the AAV-TIMP-1 treatment group compared with those in the control group (by 40%; p < 0.001) and the AAV-EGFP group (by 38.2%; p < 0.001). TIMP-1 overexpression positively affected several pathomechanisms for the development of AV both in vitro and in vivo as compared to that in the control groups: endothelium integrity was preserved as shown by zona occludens 1 and occludin staining; MMP9 expression and activity were significantly reduced (p=0.01); and smooth muscle cell migration was significantly reduced as smooth muscle actin positive cells predominantly remained in the aortic media in the treatment group (p=0.001). Moreover, macrophage infiltration was markedly reduced by 49% in the AAV-TIMP-1 group (p < 0.001). - Conclusion: Immediate post-harvesting allograft incubation with AAV-TIMP-1 reduces neointima formation and macrophage infiltration, constituting a possible adjunct therapeutic strategy to preserve graft function after transplantation.